Probabilistic buckling analysis of the beam steel structures subjected to fire by the stochastic finite element method - Świta, Piotr; Kamiński, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
The main purpose is to present the stochastic perturbation-based Finite Element Method analysis of the stability in the issues related to the influence of high temperature resulting from a fire directly connected with the reliability analysis of such structures. The thin-walled beam structures with constant cross-sectional thickness are uploaded with typical constant loads, variable loads and, additionally, a temperature increase and we look for the first critical value equivalent to the global stability loss.
Keywords: stability analysis; linearized buckling; fire simulation; stochastic perturbation method; Stochastic Finite Element Method; response function method; reliability analysis